Foaming purees as a strategy to modify oral processing time - R. Baixauli; A. Tárrega; I. Hernando; L. Laguna (Current Research in Food Science)
Food structure modification by increasing viscosity or adding heterogeneity to the food product has shown to effectively change food oral processing. In this study, it was hypothesized that the addition of gas to purees could affect oral processing. This was achieved by creating different structures in purees using a gas syphon, vacuum and syphon + vacuum. The physical properties of the puree (density, flow and mechanical properties) as well as oral processing characteristics, sensory perception and hunger profiles were investigated. Physical measurements showed that the incorporation of gas affected the puree structure as evidenced by a decrease in viscosity, hardness and consistency of the purees. At the oral level, these foamed purees took longer to swallow, which was also reflected in a lower eating rate and slightly lower amount consumed. These changes did not affect hunger or satiety. Therefore, this technique could be beneficial for people who need to eat smaller amounts of food, or for people with swallowing problems, for whom more time in the mouth is recommended without an increase in sensory satiety.